Netizens’ Responses towards the Covid-19 Pandemic Text: A Study of Speech Acts and Their Contents - Rahmatika, Laily; Wahyudi, Agus Budi (Journal of Pragmatics Research, 2020)
The case of increasing the corona-virus cluster circulating on social media has reaped various responses from netizens. The research objectives: (1) Determine the form of speech acts in netizens’ responses towards the Covid-19 pandemic text (2) Describe the content in netizens’ responses towards the Covid-19 pandemic text. The research data are in the form of sentences (speech acts) and sentences containing the substance or content of the netizens’ responses. Data sources are as many as 180 netizens’ responses on Instagram and Facebook. The data are collected by reading and taking notes of techniques. The method of data analysis is using a distribution method which is dividing the elements directly and the equivalent method with pragmatic techniques. The results: First, speech acts in netizens’ responses as locutionary acts, illocutionary acts, and perlocutionary acts. Second, the content responses from netizens. i. optimistic ii. pessimistic iii. neutral.Keywords: Netizens Response, Covid-19, Speech act, Content